Shape memory composite material and preparation method thereof
By adopting a multi-layer composite structure and a modified glass fiber fabric layer in the shape memory composite, the problems of high stiffness and poor deformation ability of carbon fiber reinforced shape memory composite are solved, and wider applications and higher deformation ability are achieved.
Patent Information
- Application Number
- CN202411496311.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing carbon fiber reinforced shape memory composite materials have a large overall stiffness, resulting in small damage strain above the material shape memory transition temperature, poor deformation ability, unable to meet the needs of large deformation, and low folding efficiency, limiting its application range.
A multi-layer composite structure is adopted, a glass fiber fabric layer is added, and the binding force between the glass fiber fabric and polyurethane shape memory polymer is improved through modification treatment, reducing the elastic modulus of the material, and improving deformation ability. The specific method includes alternately laying carbon fiber fabric and glass fiber fabric between the upper composite layer, the intermediate layer and the lower composite layer, connecting it with a polyurethane film layer, and preparing a shape memory composite material through a hot pressing process.
It effectively reduces the stiffness of the material, improves the deformation ability, expands the application range of shape memory composite materials, and improves the mechanical properties and shape memory properties of the material.
Smart Images

Figure CN119239067A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a shape memory composite material and a preparation method thereof. Background Art
[0002] Shape memory materials, as a new type of intelligent material that appeared in the last century, can respond to deformation caused by mechanical action under certain stimuli, such as heating or electricity, that is, recover deformation caused by mechanical action. Therefore, they have broad application prospects in the field of aerospace. They can be mainly divided into three categories: shape memory alloys (SMAs), shape memory ceramics (SMCs) and shape memory polymer composites (SMPCs). Although shape memory alloys and shape memory ceramics can achieve stable deployment and overcome the problem of poor stability of traditional space deployable structures, they still have the problems of large mass and small storage strain. In contrast, shape memory polymer composites can achieve high storage strain and strain recovery capabilities and stable deployment, and also have the advantages of low density and light mass. Therefore, shape memory polymer composites are regarded as ideal materials for new space deployable structures.
[0003] Shape memory polymer composites are mainly composed of a shape memory polymer matrix and a reinforcement phase or functional phase. The most commonly used reinforcements or functional phases are mainly divided into three categories: particles, chopped fibers and continuous fibers. Usually, particle-filled shape memory composites are used as functional materials to achieve shape memory effects in different driving modes, such as electric driving modes. Compared with particle-filled shape memory composites, chopped fiber-reinforced shape memory composites have improved mechanical properties. However, compared with continuous fibers as reinforcement phases, not only are there dispersion problems during preparation, but also they cannot meet the mechanical performance requirements of large structural materials. Therefore, when used as structural materials, continuous fibers are mainly used as reinforcement phases. Among them, carbon fibers, as a kind of continuous fibers, have the advantages of high specific strength, high specific modulus, and high thermal conductivity. Therefore, shape memory carbon fiber composites prepared with carbon fibers as reinforcements are the most widely used shape memory polymer composites.
[0004] Existing carbon fiber reinforced shape memory composite materials are mostly made by using polymers with shape memory function and continuous carbon fibers to prepare prepregs and then molding and curing them or using RTM technology. In addition, the overall stiffness of carbon fiber reinforced shape memory composite materials is relatively large, and the failure strain is small above the shape memory transition temperature of the material, resulting in poor deformation ability of the material and low folding efficiency. It has great limitations in use and cannot meet the needs of large deformation. Summary of the invention
[0005] The purpose of the present invention is to solve the above technical problems and propose a shape memory composite material and a preparation method thereof. The shape memory composite material prepared by the present invention not only has good mechanical strength, but also has good deformation ability and shape memory function.
[0006] The technical solution of the present invention is achieved in this way:
[0007] A shape memory composite material comprises an upper composite layer, an intermediate layer and a lower composite layer which are stacked in sequence, wherein the upper composite layer and the intermediate layer, and the intermediate layer and the lower composite layer are connected respectively through a polyurethane film layer.
[0008] Preferably, the upper composite layer comprises an upper carbon fiber fabric layer and a plurality of polyurethane film layers stacked on the carbon fiber fabric layer, the middle layer comprises a plurality of stacked glass fiber fabric layers, the glass fiber fabric layers are connected by polyurethane film layers, and the lower composite layer comprises a plurality of stacked polyurethane film layers and a lower carbon fiber fabric layer stacked on the polyurethane film layer.
[0009] In the prior art, the mechanical strength of the shape memory polymer can be significantly enhanced by combining carbon fiber fabric with shape memory polymer, but the prepared memory composite material has a large overall stiffness, and the failure strain is small above the shape memory transition temperature of the material, resulting in poor material deformation ability and low folding efficiency. It has large usage limitations and cannot meet the needs of large deformation. To solve this problem, the memory composite material of the present invention is provided with a multi-layer composite structure, and a glass fiber fabric layer is added to the structure, and the glass fiber fabric layer is combined with the polyurethane shape memory polymer. At the same time, the glass fiber fabric adopts the form of combining 45° glass fiber plain weave fabric and 0° glass fiber plain weave fabric, which can effectively reduce the elastic modulus of the material, that is, reduce the stiffness of the material, improve the deformation ability of the material, and expand the application range of the memory composite material.
[0010] Preferably, the upper carbon fiber fabric layer in the upper composite layer is 3K plain carbon fiber fabric, and the number of polyurethane film layers stacked on the upper carbon fiber fabric layer is 3 layers.
[0011] Preferably, the number of glass fiber fabric layers in the middle layer is 4, and the glass fiber fabric layers stacked on the top and bottom of the middle layer are 0° glass fiber plain weave fabrics, and the glass fibers in the two middle layers are 45° glass fiber plain weave fabrics.
[0012] Preferably, the number of polyurethane film layers in the lower composite layer is 3, and the lower carbon fiber fabric layer is 3K plain weave carbon fiber fabric.
[0013] A method for preparing a shape memory composite material comprises the following steps:
[0014] A polytetrafluoroethylene release cloth is laid on a clean metal base plate, and then a lower composite layer, a polyurethane film layer, an intermediate layer, a polyurethane film layer and an upper composite layer are laid in sequence from bottom to top. The metal base plate is then placed on the molding machine platform for hot pressing. The hot pressing molding parameters are a pressure of 2-10MPa, a temperature of 80-160°C, and a time of 30-60min. The shape memory composite material is then cooled to below 45°C to obtain.
[0015] The present invention adopts the film stacking method in the molding process, that is, the shape memory thermoplastic film and the continuous fiber fabric are alternately stacked, and then the shape memory composite material is prepared by hot pressing. By controlling the molding pressure and temperature, it is ensured that the melt can enter between the fiber layers and will not flow between the fiber fabric layers. Compared with resin vacuum injection molding and resin transfer molding, the shape memory composite material prepared by this method has the advantages of simple process, high production efficiency, controllable resin content, and low porosity of the composite material.
[0016] Preferably, the method for preparing the polyurethane film layer comprises the following steps:
[0017] 1) adding nano-silica to the hydrolyzate of epoxy silane coupling agent, stirring for reaction, obtaining coupling agent modified nano-silica, adding the coupling agent modified nano-silica to tetraethylene pentamine solution, heating for reaction, obtaining amino nano-silica;
[0018] 2) Mix polyoxypropylene glycol, dichlorodiphenylmethanediamine and amino nano-silica evenly, then add tetrahydrofuran, heat to 50-55° C., then add isocyanate, and stir to react;
[0019] 3) Pour the reaction solution into a mold, and then perform vulcanization and aging in sequence to obtain a polyurethane film layer.
[0020] Preferably, the glass fiber fabric layer in the intermediate layer is subjected to a modification treatment, comprising the following steps:
[0021] 1) adding polyvinyl acetate to anhydrous ethanol, heating and stirring to dissolve, to obtain a polyvinyl acetate solution, and then dropping a sodium hydroxide solution to partially alcoholyze the polyvinyl acetate, to obtain an alcoholyzed polyvinyl acetate solution;
[0022] 2) adding glutaraldehyde to the alcoholysis polyvinyl acetate solution, stirring evenly, then immersing the glass fiber fabric in the solution, dropping a hydrochloric acid solution to adjust the pH value of the solution to be acidic, heating to 40° C. to react for 8 minutes, taking out the glass fiber fabric and drying it to obtain a glass fiber fabric intermediate;
[0023] 3) placing the glass fiber fabric intermediate in a sodium hydroxide solution, then heating it for reaction, taking out the glass fiber fabric intermediate and drying it to obtain the product.
[0024] In the technical solution of the present invention, as mentioned above, by combining the glass fiber fabric layer with the polyurethane shape memory polymer, the rigidity of the shape memory polymer material is reduced and the deformation ability of the material is improved. However, due to the poor combination of the glass fiber fabric and the polyurethane shape memory polymer, the glass fiber fabric has a limited effect on improving the deformation ability of the polyurethane shape memory polymer. To solve this problem, the present invention further modifies the glass fiber fabric, firstly drips a sodium hydroxide solution into a polyvinyl acetate solution, partially hydrolyzes the polyvinyl acetate, and loads hydroxyl groups, then utilizes the cross-linking effect of glutaraldehyde to cause the hydrolyzed polyvinyl acetate to undergo a cross-linking reaction on the glass fiber fabric, and finally utilizes the hydrolysis effect of sodium hydroxide to fully hydrolyze the polyvinyl acetate on the glass fiber fabric to generate hydroxyl groups, thereby causing a large amount of hydroxyl groups to be loaded on the surface of the glass fiber fabric. On the other hand, in the process of preparing the polyurethane film, the present invention dopes the polyurethane shape memory polymer with amino nano-silicon dioxide, utilizes the hydrogen bonding force generated by the amino groups in the polymer and the hydroxyl groups on the surface of the glass fiber fabric, improves the bonding force between the glass fiber fabric layer and the polyurethane shape memory polymer, thereby reducing the rigidity of the shape memory polymer material and further improving the deformation ability of the material.
[0025] Preferably, the amount of glutaraldehyde added in step 2) is 0.8-1.6 wt % of the alcoholysed polyvinyl acetate solution.
[0026] In order to improve the deformation ability of shape memory polymer, the present invention must crosslink sufficient alcoholysis polyvinyl acetate on glass fiber fabric, so that the glass fiber fabric loads sufficient hydroxyl groups and amino groups in the polymer to form hydrogen bonding forces, thereby improving the binding ability between the two. Therefore, the present invention controls the addition amount of glutaraldehyde to be greater than 0.8wt% of the alcoholysis polyvinyl acetate solution. It was unexpectedly found during the experiment that when the addition amount of glutaraldehyde exceeds 1.6wt%, the shape memory performance (shape recovery rate) of the material is greatly reduced, which may be because the excessive alcoholysis polyvinyl acetate crosslinked on the glass fiber fabric causes the hard segment content in the polyurethane structure to decrease, thereby causing the shape memory performance of the material to decrease. Therefore, the present invention controls the addition amount of glutaraldehyde to be 0.8-1.6wt% of the alcoholysis polyvinyl acetate solution.
[0027] Preferably, in step 3), the heating temperature is 40-45° C., and the heating reaction time is 2-3 h.
[0028] The present invention has the following beneficial effects:
[0029] 1) The present invention provides a multi-layer structure for the memory composite material, and further adds a glass fiber fabric layer in the structure, combines the glass fiber fabric layer with the polyurethane shape memory polymer, and the glass fiber fabric is in the form of a combination of 45° glass fiber plain weave fabric and 0° glass fiber plain weave fabric, which can effectively reduce the elastic modulus of the material, that is, reduce the rigidity of the material, improve the deformation ability of the material, and expand the application scope of the memory composite material;
[0030] 2) The present invention adopts a film lamination method in the molding process, that is, shape memory thermoplastic film and continuous fiber fabric are alternately stacked, and then the shape memory composite material is prepared by hot pressing. By controlling the molding pressure and temperature, it is ensured that the melt can enter between the fiber layers and will not flow between the fiber fabric layers;
[0031] 3) During the preparation of the polyurethane film, amino-modified nano-silica is doped into the polyurethane shape memory polymer. The hydrogen bonding force generated by the amino groups in the polymer and the hydroxyl groups on the surface of the modified glass fiber fabric is utilized to increase the bonding force between the glass fiber fabric layer and the polyurethane shape memory polymer, thereby reducing the stiffness of the shape memory polymer material and further improving the deformation ability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of the shape memory composite material of the present invention.
[0033] Reference numerals
[0034] An upper composite layer 100 , an intermediate layer 200 , a lower composite layer 300 , a polyurethane film layer 400 , an upper carbon fiber fabric layer 101 , a glass fiber fabric layer 201 , and a lower carbon fiber fabric layer 301 . DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In a specific embodiment of the present invention, the 3K plain woven carbon fiber fabric is a T300-grade continuous carbon fiber fabric with an area density of 200 g / m2, and the area density of the glass fiber plain woven fabric is 400 g / m2.
[0037] A shape memory composite material comprises an upper composite layer 100, an intermediate layer 200 and a lower composite layer 300 stacked in sequence, wherein the upper composite layer and the intermediate layer, and the intermediate layer and the lower composite layer are respectively connected by a polyurethane film layer 400, wherein the upper composite layer comprises an upper carbon fiber fabric layer 101 and three polyurethane film layers 400 stacked on the carbon fiber fabric layer, wherein the upper carbon fiber fabric layer in the upper composite layer is a 3K plain carbon fiber fabric. The intermediate layer comprises four stacked glass fiber fabric layers 201, wherein the glass fiber fabric layers are connected by a polyurethane film layer 400, wherein the glass fiber fabric layers stacked on the top and bottom of the intermediate layer are 0° glass fiber plain fabrics, and the glass fibers in the middle two layers are 45° glass fiber plain fabrics. The lower composite layer comprises three stacked polyurethane film layers 400 and a lower carbon fiber fabric layer 301 stacked on the polyurethane film layer, wherein the lower carbon fiber fabric layer is a 3K plain carbon fiber fabric.
[0038] Example 1
[0039] A method for preparing a shape memory composite material comprises the following steps:
[0040] A polytetrafluoroethylene release cloth is laid on a clean metal base plate, and then three layers of stacked polyurethane film layer, lower carbon fiber fabric layer, polyurethane film layer, 0° glass fiber plain fabric layer, polyurethane film layer, 45° glass fiber plain fabric layer, polyurethane film layer, 45° glass fiber plain fabric layer, polyurethane film layer, 0° glass fiber plain fabric layer, polyurethane film layer, upper carbon fiber fabric layer, and three layers of stacked polyurethane film layer are laid in sequence from bottom to top. The metal base plate is placed on the molding machine platform for hot pressing molding, and the hot pressing molding parameters are pressure 8MPa, temperature 130℃, time 50min, and then cooled to 40℃ to obtain a shape memory composite material.
[0041] The preparation method of the polyurethane film layer comprises the following steps:
[0042] 1) adding silane coupling agent KH560 to deionized water at a mass ratio of 1:30, heating to 50° C., stirring to obtain an epoxy silane coupling agent hydrolyzate, and then adding nano-silica to the epoxy silane coupling agent hydrolyzate at a mass volume ratio of 1 g / 50 mL, stirring to react for 2 hours, to obtain coupling agent modified nano-silica;
[0043] The coupling agent-modified nano-silica was added into a 3% tetraethylenepentamine aqueous solution at a mass volume ratio of 1 g / 60 mL, heated to 80° C., and stirred for reaction for 3 h to obtain amino-modified nano-silica;
[0044] 2) Polyoxypropylene glycol, dichlorodiphenylmethane diamine and amino nano-silica were mixed uniformly in a mass ratio of 20:5:3, and then tetrahydrofuran was added, the mass volume ratio of polyoxypropylene glycol to tetrahydrofuran was 1g / 500mL, and the mixture was heated to 53°C, and then isocyanate was added, the mass ratio of polyoxypropylene glycol to isocyanate was 1:2, and the mixture was stirred for reaction for 20 minutes;
[0045] 3) The reaction solution was poured into a mold, vulcanized at 80° C. for 3 h, and then aged at room temperature for 10 days to obtain a polyurethane film layer.
[0046] The glass fiber plain woven fabric layer is modified by the following steps:
[0047] 1) adding polyvinyl acetate to anhydrous ethanol, heating and stirring to dissolve, preparing a polyvinyl acetate solution with a mass concentration of 5%, and then dropping a 30wt% sodium hydroxide ethanol solution for alcoholysis for 20 minutes, wherein the volume ratio of the sodium hydroxide solution to the polyvinyl acetate solution is 1:30;
[0048] 2) adding glutaraldehyde to the alcoholysis polyvinyl acetate solution, wherein the amount of glutaraldehyde added is 1.4 wt % of the alcoholysis polyvinyl acetate solution, stirring the mixture evenly, then immersing a glass fiber fabric in the solution at a bath ratio of 1:50, dropping a hydrochloric acid solution to adjust the solution pH to 3, heating the solution to 40° C. for reaction for 8 min, taking out the glass fiber fabric and drying the same at 70° C. to obtain a glass fiber fabric intermediate;
[0049] 3) placing the glass fiber fabric intermediate in a 20 wt % sodium hydroxide aqueous solution at a bath ratio of 1:30, then heating to 45° C., reacting for 2.5 hours, taking out the glass fiber fabric intermediate and drying it at 50° C. to obtain the product.
[0050] Example 2
[0051] A method for preparing a shape memory composite material comprises the following steps:
[0052] A polytetrafluoroethylene release cloth is laid on a clean metal base plate, and then three layers of stacked polyurethane film layer, lower carbon fiber fabric layer, polyurethane film layer, 0° glass fiber plain fabric layer, polyurethane film layer, 45° glass fiber plain fabric layer, polyurethane film layer, 45° glass fiber plain fabric layer, polyurethane film layer, 0° glass fiber plain fabric layer, polyurethane film layer, upper carbon fiber fabric layer, and three layers of stacked polyurethane film layer are laid in sequence from bottom to top. The metal base plate is placed on the molding machine platform for hot pressing molding, and the hot pressing molding parameters are pressure 3MPa, temperature 90℃, time 40min, and then cooled to 40℃ to obtain a shape memory composite material.
[0053] The preparation method of the polyurethane film layer comprises the following steps:
[0054] 1) adding silane coupling agent KH560 to deionized water at a mass ratio of 1:30, heating to 50° C., stirring to obtain an epoxy silane coupling agent hydrolyzate, and then adding nano-silica to the epoxy silane coupling agent hydrolyzate at a mass volume ratio of 1 g / 50 mL, stirring to react for 2 hours, to obtain coupling agent modified nano-silica;
[0055] The coupling agent-modified nano-silica was added into a 3% tetraethylenepentamine aqueous solution at a mass volume ratio of 1 g / 60 mL, heated to 80° C., and stirred for reaction for 3 h to obtain amino-modified nano-silica;
[0056] 2) Polyoxypropylene glycol, dichlorodiphenylmethane diamine and amino nano-silica were mixed uniformly in a mass ratio of 20:5:3, and then tetrahydrofuran was added, the mass volume ratio of polyoxypropylene glycol to tetrahydrofuran was 1g / 500mL, and the mixture was heated to 53°C, and then isocyanate was added, the mass ratio of polyoxypropylene glycol to isocyanate was 1:2, and the mixture was stirred for reaction for 20 minutes;
[0057] 3) The reaction solution was poured into a mold, vulcanized at 80° C. for 3 h, and then aged at room temperature for 10 days to obtain a polyurethane film layer.
[0058] The glass fiber plain woven fabric layer is modified by the following steps:
[0059] 2) adding polyvinyl acetate to anhydrous ethanol, heating and stirring to dissolve, preparing a polyvinyl acetate solution with a mass concentration of 5%, and then dropping a 30wt% sodium hydroxide ethanol solution for alcoholysis for 20 minutes, wherein the volume ratio of the sodium hydroxide solution to the polyvinyl acetate solution is 1:30;
[0060] 2) adding glutaraldehyde to the alcoholysis polyvinyl acetate solution, wherein the amount of glutaraldehyde added is 1.0wt% of the alcoholysis polyvinyl acetate solution, and stirring the mixture evenly; then immersing a glass fiber fabric in the solution according to a bath ratio of 1:50, dripping a hydrochloric acid solution to adjust the pH value of the solution to 3, heating the solution to 40° C. to react for 8 minutes, taking out the glass fiber fabric and drying the same at 70° C. to obtain a glass fiber fabric intermediate;
[0061] 3) placing the glass fiber fabric intermediate in a 20 wt % sodium hydroxide aqueous solution at a bath ratio of 1:30, then heating to 45° C., reacting for 2.5 hours, taking out the glass fiber fabric intermediate and drying it at 50° C. to obtain the product.
[0062] Example 3
[0063] A method for preparing a shape memory composite material comprises the following steps:
[0064] A polytetrafluoroethylene release cloth is laid on a clean metal base plate, and then three layers of stacked polyurethane film layer, lower carbon fiber fabric layer, polyurethane film layer, 0° glass fiber plain weave fabric layer, polyurethane film layer, 45° glass fiber plain weave fabric layer, polyurethane film layer, 45° glass fiber plain weave fabric layer, polyurethane film layer, 0° glass fiber plain weave fabric layer, polyurethane film layer, upper carbon fiber fabric layer, and three layers of stacked polyurethane film layer are laid in sequence from bottom to top. The metal base plate is placed on the molding machine platform for hot pressing molding, and the hot pressing molding parameters are pressure 2MPa, temperature 130℃, time 30min, and then cooled to 40℃ to obtain a shape memory composite material.
[0065] The preparation method of the polyurethane film layer comprises the following steps:
[0066] 1) adding silane coupling agent KH560 to deionized water at a mass ratio of 1:30, heating to 50° C., stirring to obtain an epoxy silane coupling agent hydrolyzate, and then adding nano-silica to the epoxy silane coupling agent hydrolyzate at a mass volume ratio of 1 g / 50 mL, stirring to react for 2 hours, to obtain coupling agent modified nano-silica;
[0067] The coupling agent-modified nano-silica was added into a 3% tetraethylenepentamine aqueous solution at a mass volume ratio of 1 g / 60 mL, heated to 80° C., and stirred for reaction for 3 h to obtain amino-modified nano-silica;
[0068] 2) Polyoxypropylene glycol, dichlorodiphenylmethane diamine and amino nano-silica were mixed uniformly in a mass ratio of 20:5:3, and then tetrahydrofuran was added, the mass volume ratio of polyoxypropylene glycol to tetrahydrofuran was 1g / 500mL, and the mixture was heated to 53°C, and then isocyanate was added, the mass ratio of polyoxypropylene glycol to isocyanate was 1:2, and the mixture was stirred for reaction for 20 minutes;
[0069] 3) The reaction solution was poured into a mold, vulcanized at 80° C. for 3 h, and then aged at room temperature for 10 days to obtain a polyurethane film layer.
[0070] The glass fiber plain woven fabric layer is modified by the following steps:
[0071] 3) adding polyvinyl acetate to anhydrous ethanol, heating and stirring to dissolve, preparing a polyvinyl acetate solution with a mass concentration of 5%, and then dropping a 30wt% sodium hydroxide ethanol solution to perform alcoholysis for 20 minutes, wherein the volume ratio of the sodium hydroxide solution to the polyvinyl acetate solution is 1:30;
[0072] 2) adding glutaraldehyde to the alcoholysis polyvinyl acetate solution, wherein the amount of glutaraldehyde added is 1.2 wt % of the alcoholysis polyvinyl acetate solution, stirring the mixture evenly, then immersing a glass fiber fabric in the solution at a bath ratio of 1:50, dropping a hydrochloric acid solution to adjust the solution pH to 3, heating the solution to 40° C. for reaction for 8 min, taking out the glass fiber fabric and drying the same at 70° C. to obtain a glass fiber fabric intermediate;
[0073] 3) placing the glass fiber fabric intermediate in a 20 wt % sodium hydroxide aqueous solution at a bath ratio of 1:30, then heating to 45° C., reacting for 2.5 hours, taking out the glass fiber fabric intermediate and drying it at 50° C. to obtain the product.
[0074] Example 4
[0075] A method for preparing a shape memory composite material comprises the following steps:
[0076] A polytetrafluoroethylene release cloth is laid on a clean metal base plate, and then three layers of stacked polyurethane film layer, lower carbon fiber fabric layer, polyurethane film layer, 0° glass fiber plain fabric layer, polyurethane film layer, 45° glass fiber plain fabric layer, polyurethane film layer, 45° glass fiber plain fabric layer, polyurethane film layer, 0° glass fiber plain fabric layer, polyurethane film layer, upper carbon fiber fabric layer, and three layers of stacked polyurethane film layers are laid in sequence from bottom to top. The metal base plate is placed on the molding machine platform for hot pressing molding, and the hot pressing molding parameters are pressure 10MPa, temperature 160℃, time 60min, and then cooled to below 45℃ to obtain a shape memory composite material.
[0077] The preparation method of the polyurethane film layer comprises the following steps:
[0078] 1) adding silane coupling agent KH560 to deionized water at a mass ratio of 1:30, heating to 50° C., stirring to obtain an epoxy silane coupling agent hydrolyzate, and then adding nano-silica to the epoxy silane coupling agent hydrolyzate at a mass volume ratio of 1 g / 50 mL, stirring to react for 2 hours, to obtain coupling agent modified nano-silica;
[0079] The coupling agent-modified nano-silica was added into a 3% tetraethylenepentamine aqueous solution at a mass volume ratio of 1 g / 60 mL, heated to 80° C., and stirred for reaction for 3 h to obtain amino-modified nano-silica;
[0080] 2) Polyoxypropylene glycol, dichlorodiphenylmethane diamine and amino nano-silica were mixed uniformly in a mass ratio of 20:5:3, and then tetrahydrofuran was added, the mass volume ratio of polyoxypropylene glycol to tetrahydrofuran was 1g / 500mL, and the mixture was heated to 55°C, and then isocyanate was added, the mass ratio of polyoxypropylene glycol to isocyanate was 1:2, and the mixture was stirred for reaction for 20 minutes;
[0081] 3) The reaction solution was poured into a mold, vulcanized at 80° C. for 3 h, and then aged at room temperature for 10 days to obtain a polyurethane film layer.
[0082] The glass fiber plain woven fabric layer is modified by the following steps:
[0083] 4) adding polyvinyl acetate to anhydrous ethanol, heating and stirring to dissolve, preparing a polyvinyl acetate solution with a mass concentration of 5%, and then dropping a 30wt% sodium hydroxide ethanol solution to perform alcoholysis for 20 minutes, wherein the volume ratio of the sodium hydroxide solution to the polyvinyl acetate solution is 1:30;
[0084] 2) adding glutaraldehyde to the alcoholysis polyvinyl acetate solution, wherein the amount of glutaraldehyde added is 1.6 wt % of the alcoholysis polyvinyl acetate solution, stirring the mixture evenly, then immersing a glass fiber fabric in the solution at a bath ratio of 1:50, dropping a hydrochloric acid solution to adjust the solution pH to 3, heating the solution to 40° C. for reaction for 8 min, taking out the glass fiber fabric and drying the same at 70° C. to obtain a glass fiber fabric intermediate;
[0085] 3) placing the glass fiber fabric intermediate in a 20 wt % sodium hydroxide aqueous solution at a bath ratio of 1:30, then heating to 50° C. and reacting for 3 hours, taking out the glass fiber fabric intermediate and drying it at 50° C. to obtain the product.
[0086] Example 5
[0087] A method for preparing a shape memory composite material comprises the following steps:
[0088] A polytetrafluoroethylene release cloth is laid on a clean metal base plate, and then three layers of stacked polyurethane film layer, lower carbon fiber fabric layer, polyurethane film layer, 0° glass fiber plain fabric layer, polyurethane film layer, 45° glass fiber plain fabric layer, polyurethane film layer, 45° glass fiber plain fabric layer, polyurethane film layer, 0° glass fiber plain fabric layer, polyurethane film layer, upper carbon fiber fabric layer, and three layers of stacked polyurethane film layer are laid in sequence from bottom to top. The metal base plate is placed on the molding machine platform for hot pressing molding, and the hot pressing molding parameters are pressure 2MPa, temperature 80℃, time 30min, and then cooled to below 45℃ to obtain a shape memory composite material.
[0089] The preparation method of the polyurethane film layer comprises the following steps:
[0090] 1) adding silane coupling agent KH560 to deionized water at a mass ratio of 1:30, heating to 50° C., stirring to obtain an epoxy silane coupling agent hydrolyzate, and then adding nano-silica to the epoxy silane coupling agent hydrolyzate at a mass volume ratio of 1 g / 50 mL, stirring to react for 2 hours, to obtain coupling agent modified nano-silica;
[0091] The coupling agent-modified nano-silica was added into a 3% tetraethylenepentamine aqueous solution at a mass volume ratio of 1 g / 60 mL, heated to 80° C., and stirred for reaction for 3 h to obtain amino-modified nano-silica;
[0092] 2) Polyoxypropylene glycol, dichlorodiphenylmethane diamine and amino nano-silica were mixed uniformly in a mass ratio of 20:5:3, and then tetrahydrofuran was added, the mass volume ratio of polyoxypropylene glycol to tetrahydrofuran was 1g / 500mL, and the mixture was heated to 50°C, and then isocyanate was added, the mass ratio of polyoxypropylene glycol to isocyanate was 1:2, and the mixture was stirred for reaction for 20 minutes;
[0093] 3) The reaction solution was poured into a mold, vulcanized at 80° C. for 3 h, and then aged at room temperature for 10 days to obtain a polyurethane film layer.
[0094] The glass fiber plain woven fabric layer is modified by the following steps:
[0095] 5) adding polyvinyl acetate to anhydrous ethanol, heating and stirring to dissolve, preparing a polyvinyl acetate solution with a mass concentration of 5%, and then dropping a 30wt% sodium hydroxide ethanol solution to perform alcoholysis for 20 minutes, wherein the volume ratio of the sodium hydroxide solution to the polyvinyl acetate solution is 1:30;
[0096] 2) adding glutaraldehyde to the alcoholysis polyvinyl acetate solution, wherein the amount of glutaraldehyde added is 0.8wt% of the alcoholysis polyvinyl acetate solution, and stirring the mixture evenly; then immersing a glass fiber fabric in the solution according to a bath ratio of 1:50; dripping a hydrochloric acid solution to adjust the solution pH to 3; heating the solution to 40° C. for reaction for 8 min; taking out the glass fiber fabric and drying the same at 70° C. to obtain a glass fiber fabric intermediate;
[0097] 3) placing the glass fiber fabric intermediate in a 20 wt % sodium hydroxide aqueous solution at a bath ratio of 1:30, then heating to 40° C., reacting for 2 h, taking out the glass fiber fabric intermediate and drying it at 50° C. to obtain the product.
[0098] Comparative Example 1
[0099] The difference between Comparative Example 1 and Example 1 is:
[0100] During the preparation of the shape memory composite material, the upper and lower carbon fiber fabric layers are not stacked, and the remaining operation steps are the same as those in Example 1.
[0101] Comparative Example 2
[0102] The difference between Comparative Example 2 and Example 1 is:
[0103] In the preparation process of shape memory composite materials, glass fiber plain woven fabric layers are not stacked.
[0104] The remaining steps are the same as those in Example 1.
[0105] Comparative Example 3
[0106] The difference between Comparative Example 3 and Example 1 is that:
[0107] Step 1) is omitted in the preparation process of the polyurethane film layer.
[0108] The amino-treated nano-silicon dioxide in step 2) is replaced with ordinary nano-silicon dioxide.
[0109] The remaining steps are the same as those in Example 1.
[0110] Comparative Example 4
[0111] The difference between Comparative Example 4 and Example 1 is that:
[0112] The glass fiber plain weave fabric layer has not been modified.
[0113] The remaining steps are the same as those in Example 1.
[0114] Comparative Example 5
[0115] The difference between Comparative Example 5 and Example 4 is that:
[0116] In the modification method of glass fiber plain woven fabric layer,
[0117] The amount of glutaraldehyde added is 1.7wt% of the alcoholysed polyvinyl acetate solution.
[0118] The remaining steps are the same as those in Example 4.
[0119] Performance Testing
[0120] 1. Mechanical strength test:
[0121] The sheet-like shape memory composite material was cut into dumbbell shape according to the standard of GB / T1040-92, with a length of L = 115 mm, a length of the middle parallel narrow strip part L1 = 33 mm, an end width W = 25 mm, a narrow part width W0 = 6 mm, and a sample thickness D = 2 mm. The tensile strength of the shape memory composite material was tested according to the test method of GB / T9341-2008 (tensile rate 2 mm / min), and the impact resistance of the shape memory composite material was tested according to GB / T1043.1-2008 (pendulum energy 4 J). The test structure is shown in Table 1.
[0122] Table 1:
[0123]
[0124] 2. Stiffness test
[0125] The stiffness of the shape memory composite material is characterized by the elastic modulus. The larger the elastic modulus, the higher the stiffness of the shape memory composite material. The elastic modulus test is carried out according to the method in GB / T 1040.1-2006. The test results are shown in Table 2.
[0126] Table 2
[0127]
[0128] 3. Shape memory performance test
[0129] The shape memory performance of the composite material is tested by the bending method. The specific method is to first cut the sample into 100mmx20mmX2mm strips, put it into the oven at a predetermined temperature and heat it for 5 minutes to soften it. In order to fix the uniform deformation, put the strip into a 10mL beaker and bend it into a "U" shape. The bending angle at this time is recorded as 180°. The beaker is quickly placed in an ice water bath (5°C). After cooling for 5 minutes, the strip is taken out and placed at room temperature for 2 hours. The shape recovery of the sample is observed and the bending angle at this time is recorded as N1. Finally, the strip is placed in the oven at a predetermined temperature again, and the timing is started to observe the angle recovery until the angle no longer changes. The bending angle at this time is recorded as N2. The shape fixity and shape recovery of the material are calculated according to the following formula:
[0130] Shape fixity (%) = N1 / 180°X100%;
[0131] Shape recovery (%) = (180°-N2) / 180°X100%;
[0132] The test and calculation results are shown in Table 3.
[0133] Table 3:
[0134]
[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A shape memory composite material, characterized in that: It comprises an upper composite layer (100), an intermediate layer (200) and a lower composite layer (300) which are stacked in sequence, wherein the upper composite layer and the intermediate layer, and the intermediate layer and the lower composite layer are connected respectively via a polyurethane film layer (400).
2. The shape memory composite material according to claim 1, characterized in that: The upper composite layer comprises an upper carbon fiber fabric layer (101) and a plurality of polyurethane film layers (400) stacked on the carbon fiber fabric layer; the middle layer comprises a plurality of stacked glass fiber fabric layers (201), wherein the glass fiber fabric layers are connected by polyurethane film layers (400); and the lower composite layer comprises a plurality of stacked polyurethane film layers (400) and a lower carbon fiber fabric layer (301) stacked on the polyurethane film layer.
3. The shape memory composite material according to claim 1, characterized in that: The upper carbon fiber fabric layer in the upper composite layer is 3K plain carbon fiber fabric, and the number of polyurethane film layers stacked on the upper carbon fiber fabric layer is 3 layers.
4. The shape memory composite material according to claim 1, characterized in that: The number of glass fiber fabric layers in the middle layer is 4, and the glass fiber fabric layers stacked on the top and bottom of the middle layer are 0° glass fiber plain weave fabrics, and the glass fibers in the two middle layers are 45° glass fiber plain weave fabrics.
5. The shape memory composite material according to claim 1, characterized in that: The number of polyurethane film layers in the lower composite layer is 3, and the lower carbon fiber fabric layer is 3K plain weave carbon fiber fabric.
6. A method for preparing a shape memory composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: A polytetrafluoroethylene release cloth is laid on a clean metal base plate, and then a lower composite layer, a polyurethane film layer, an intermediate layer, a polyurethane film layer and an upper composite layer are laid in sequence from bottom to top. The metal base plate is then placed on the molding machine platform for hot pressing. The hot pressing molding parameters are a pressure of 2-10MPa, a temperature of 80-160°C, and a time of 30-60min. The shape memory composite material is then cooled to below 45°C to obtain.
7. The method for preparing a shape memory composite material according to claim 6, characterized in that: The preparation method of the polyurethane film layer comprises the following steps: 1) adding nano-silica to the hydrolyzate of epoxy silane coupling agent, stirring for reaction, obtaining coupling agent modified nano-silica, adding the coupling agent modified nano-silica to tetraethylene pentamine solution, heating for reaction, obtaining amino nano-silica; 2) Mix polyoxypropylene glycol, dichlorodiphenylmethanediamine and amino nano-silica evenly, then add tetrahydrofuran, heat to 50-55° C., then add isocyanate, and stir to react; 3) Pour the reaction solution into a mold, and then perform vulcanization and aging in sequence to obtain a polyurethane film layer.
8. The method for preparing a shape memory composite material according to claim 6, characterized in that: The glass fiber fabric layer in the middle layer is subjected to a modification treatment, comprising the following steps: 1) adding polyvinyl acetate to anhydrous ethanol, heating and stirring to dissolve, to obtain a polyvinyl acetate solution, and then dropping a sodium hydroxide solution to partially alcoholyze the polyvinyl acetate, to obtain an alcoholyzed polyvinyl acetate solution; 2) adding glutaraldehyde to the alcoholysis polyvinyl acetate solution, stirring evenly, then immersing the glass fiber fabric in the solution, dropping a hydrochloric acid solution to adjust the pH value of the solution to be acidic, heating to 40° C. to react for 8 minutes, taking out the glass fiber fabric and drying it to obtain a glass fiber fabric intermediate; 3) placing the glass fiber fabric intermediate in a sodium hydroxide solution, then heating it for reaction, taking out the glass fiber fabric intermediate and drying it to obtain the product.
9. The method for preparing a shape memory composite material according to claim 8, characterized in that: The amount of glutaraldehyde added in step 2) is 0.8-1.6 wt % of the alcoholysed polyvinyl acetate solution.
10. The method for preparing a shape memory composite material according to claim 8, characterized in that: In the step 3), the heating temperature is 40-45° C. and the heating reaction time is 2-3 hours.
Citation Information
Patent Citations
Shape memory spacer fabric composite
CN109109392A
Hybrid fabric shape memory composite material structure capable of reducing bending fracture
CN218660832U
Shape memory composite material and its manufacturing method
JP2007268940A
Beam projector housing equipped with automatic cleaning function of viewing window by rotation
KR102591053B1